The Picture of Dorian Gray - Wilde, Oscar (Pakistan Readings, 2017)
Dorian Gray, the subject of a local artist's oil paintings, sells his soul so that his body never ages, while a portrait of him withers and grows old.
Keywords: Portraits -- Conduct of life -- Youthfulness